PENGARUH PERENCANAAN PAJAK, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI PADA TAHUN 2017-2021 - Raja Fadhel Al - Faraby Tjakraprajitna; Murtanto Murtanto; Hotman Tohir Pohan (STMIK Widuri Jakarta, 2023)
The purpose of this study is to examine and explain the effect of tax planning, leverage, and company size on manufacturing companies in the consumer goods industry sector which are listed at the Indonesian Stock Exchange in 2017-2021. This research was conducted at the Indonesia Stock Exchange for manufacturing companies in the consumer goods industry sector using secondary data and a purposive sampling method. The data analysis method used is quantitative analysis using descriptive statistics, panel data regression analysis, and hypothesis testing using E-views version 10. The results of this research show that tax planning and firm size have no significant effect on earnings management. Leverage have a no significant effect on earnings management. Simultaneously tax planning, leverage, and firm size affect earnings management.